BMP-9 Modulates the Hepatic Responses to LPS - Gaitantzi, Haristi; Karch, Julius; Germann, Lena; Cai, Chen; Rausch, Vanessa; Birgin, Emrullah; Rahbari, Nuh; Seitz, Tatjana; Hellerbrand, Claus; Koenig, Courtney; Augustin, Hellmut G.; Mogler, Carolin; et al. (Cells, 2020)
It was previously shown that Bone Morphogenetic Protein (BMP)-9 is constitutively produced and secreted by hepatic stellate cells (HSC). Upon acute liver damage, BMP-9 expression is transiently down-regulated and blocking BMP-9 under conditions of chronic damage ameliorated liver fibrogenesis in C57BL/6 mice. Thereby, BMP-9 acted as a pro-fibrogenic cytokine in the liver but without directly activating isolated HSC in vitro. Lipopolysaccharide (LPS), an endotoxin derived from the membrane of Gram-negative bacteria in the gut, is known to be essential in the pathogenesis of diverse kinds of liver diseases. The aim of the present project was therefore to investigate how high levels of BMP-9 in the context of LPS signalling might result in enhanced liver damage. For this purpose, we stimulated human liver sinusoidal endothelial cells (LSEC) with LPS and incubated primary human liver myofibroblasts (MF) with the conditioned medium of these cells. We found that LPS led to the secretion of factors from LSEC that upregulate BMP-9 expression in MF. At least one of these BMP-9 enhancing factors was defined to be IL-6. High BMP-9 in turn, especially in combination with LPS stimulation, induced the expression of certain capillarization markers in LSEC and enhanced the LPS-mediated induction of pro-inflammatory cytokines in primary human macrophages. In LSEC, pre-treatment with BMP-9 reduced the LPS-mediated activation of the NfkB pathway, whereas in macrophages, LPS partially inhibited the BMP-9/Smad-1 signaling cascade. In vivo, in mice, BMP-9 led to the enhanced presence of F4/80-positive cells in the liver and it modulated the LPS-mediated regulation of inflammatory mediators. In summary, our data point to BMP-9 being a complex and highly dynamic modulator of hepatic responses to LPS: Initial effects of LPS on LSEC led to the upregulation of BMP-9 in MF but sustained high levels of BMP-9 in turn promote pro-inflammatory reactions of macrophages. Thereby, the spatial and timely fine-tuned presence (or absence) of BMP-9 is needed for efficient wound-healing responses in the liver.
CRIS-Team WoS Importer:2020-05-15